2022
DOI: 10.1158/0008-5472.can-22-1329
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Digital Models Forecast Patient-Specific Treatment Responses to Neoadjuvant Chemotherapy in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is persistently refractory to therapy, and methods to improve targeting and evaluation of responses to therapy in this disease are needed. Here, we integrate quantitative magnetic resonance imaging (MRI) data with biologically-based mathematical modeling to accurately predict the response of TNBC to neoadjuvant systemic therapy (NAST) on an individual basis. Specifically, 56 TNBC patients enrolled in the ARTEMIS trial (NCT02276443) underwent standard-of-care doxorubicin/cyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…In contrast, previous studies only used conventional clinical and radiologic characteristics and did not perform precise subtypes analysis, or only used radiomics method. 49 , 50 , 51 , 52 Secondly, we collected longitudinal MRI data, including pre-NAC and post-NAC sequences, which contained the tumor change information during NAC, rather than single-modality models. 53 Previous study also reported that delta-radiomics had higher performance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, previous studies only used conventional clinical and radiologic characteristics and did not perform precise subtypes analysis, or only used radiomics method. 49 , 50 , 51 , 52 Secondly, we collected longitudinal MRI data, including pre-NAC and post-NAC sequences, which contained the tumor change information during NAC, rather than single-modality models. 53 Previous study also reported that delta-radiomics had higher performance.…”
Section: Discussionmentioning
confidence: 99%
“…According to a comparative study, the performance of radiomic‐based models, which employ MRI features, was superior to that of biologically based models using tumor cell features in predicting the response to neoadjuvant chemotherapy in triple‐negative breast cancer. The radiomic models achieved an impressive AUC of 0.89 37 . Nonetheless, the majority of the studies have predominantly utilized handcrafted radiomic features as the input for their models.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pCR of NAC can be predicted from different perspectives, including whole-slide biopsy images [ 24 ], genomic features [ 25 ], and even radiological features from pre- [ 26 ] and mid-treatment magnetic resonance imaging (MRI) [ 27 ]. Based on these parameters, quite a few prediction models have been built [ 28 , 29 ]; however, the prognostic biomarkers involved in most models are not accessible to every patient for economic reasons or due to the cumbersome steps involved. These reasons limited the assessment of which of the NAC-treated patients would have a good response.…”
Section: Introductionmentioning
confidence: 99%